Mechanical and barrier properties of Tapioca/PVA composite films reinforced with pineapple leaf nanocellulose. (January 2020) - Listyarini, A; Fauzia, V; Imawan, C
Abstract: Studies on mechanical and barrier properties of Tapioca/PVA composites reinforced with pineapple leaf nanocellulose have been done to obtain an alternative new biodegradable label for freshness label of smart packaging for food. The aim of this research is to investigate changes of mechanical and barrier properties of Tapioca/PVA/Nanocellulose compared with Tapioca/PVA composite. Composition of Tapioca/PVA was 50:50 with nanocellulose concentration vary from 1, 3, 6 and 10% in composites. Tensile strength and elongation were used to evaluate the mechanical properties of the films. While for water barrier properties was investigated by vapor transmission rate. The microstructure of the films was evaluated by using FT-IR, and SEM. The results showed that increasing the concentration of nanocellulose decreasing the tensile strength and elongation of composites. The concentration of 1% nanocellulose increased the WVTR and in greater amount will reduce the value of WVTR. Addition of nanocellulose decreased the transparency of the composite films. For further application, it can be used as a label for freshness label of smart packaging with the addition of functional material.